Analysis of DigiDes Use and Community Satisfaction in Halong Village: Public Service and Local Governance Perspective - Jefri Wael; Pieter Sammy Soselisa; Iriane Sosiawaty Ponto (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to analyze how the use of the DigiDes digital village service application influences community satisfaction in Negeri Halong, Baguala District, Ambon City. Methodology: This study employed a quantitative approach using a structured questionnaire distributed to DigiDes users. Data were processed using the IBM SPSS Statistics 25 software, utilizing validity tests, reliability tests, descriptive analysis, and simple linear regression to measure the influence of the application on community satisfaction. Main Findings: The results showed that the use of the DigiDes application has a positive and significant influence on community satisfaction, particularly in terms of service efficiency, accessibility, and accuracy. Increased use of DigiDes corresponds to higher satisfaction levels, indicating strong community acceptance of digital public services. These findings suggest improvements in village governance through more transparent and responsive services, strengthened state–citizen relations, and ongoing digital-based social transformation at the village level. Novelty/Originality of this study: This study provides new insights into how digital village service applications operate in small-scale community settings, specifically in Negeri Halong. It contributes to the development of knowledge on grassroots digital governance and demonstrates how localized digital innovations can enhance service quality and citizen satisfaction in rural and semi-urban Indonesian contexts.